Ultra-thin glass and chemically strengthened ultra-thin glass, and preparation method and application thereof
Patent Information
- Application Number
- CN202611316602.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-16
AI Technical Summary
然而,此类玻璃在化学强化(离子交换)后普遍存在两个问题:一是表面压应力(CS)较低;二是应力随深度增加衰减极快,导致应力层深度(DOL)虽然不浅但近表面的压应力峰值不足,抗冲击性能差
本申请提供了一种超薄玻璃、高应力慢松弛化学强化超薄玻璃及其制备方法,解决一次成型的超薄玻璃在化学强化后表面压应力低、应力随强化时间延长衰减快的问题,通过特定的玻璃配方与合理的退火降温速率控制,使强化后的超薄玻璃兼具高CS(≥1000MPa)和缓和的应力衰减曲线。本申请提供的超薄玻璃或化学强化超薄玻璃能够满足手机盖板等领域的应用要求。
Smart Images

Figure CN122916431A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of glass technology, and more specifically, to an ultrathin glass and a chemically strengthened ultrathin glass, as well as their preparation methods and applications. Background Technology
[0002] In recent years, foldable smartphones, tablets, and other products have been continuously upgraded, and their front cover materials have gradually transitioned from early flexible polymer films (such as polyimide) to ultra-thin glass solutions with better overall performance. Ultra-thin glass (UTG), with its excellent optical transmittance and mechanical stability, has become a key material in the field of foldable electronic devices.
[0003] From the current mass production technology perspective, ultra-thin glass covers are mainly divided into two categories: one-time molding and two-time molding (chemical thinning). One-time molding ultra-thin glass (such as float glass, slotted glass, overflow glass, etc.) is widely used in display covers, photovoltaic glass, and other fields due to its high production efficiency and low cost. However, such glass generally suffers from two problems after chemical strengthening (ion exchange): firstly, the surface compressive stress (CS) is low; secondly, the stress decreases very rapidly with increasing depth, resulting in insufficient near-surface compressive stress peaks even though the depth of stress layer (DOL) is not shallow, leading to poor impact resistance. Summary of the Invention
[0004] The applicant found that the cooling process of one-piece molded glass is usually rapid cooling (air cooling or wind cooling), the glass structure is frozen at a high hypothetical temperature state, the network is loose, the compressive stress formed after ion exchange is difficult to maintain, and the stress gradient is steep in the depth direction.
[0005] Existing technologies attempt to improve the situation by adjusting the strengthening process (such as extending the strengthening time and increasing the molten salt temperature), but the effects are limited and often lead to an excessively deep stress layer and a decrease in surface compressive stress. More importantly, glass formulations suitable for one-time molding and capable of achieving high stress are still imperfect, and existing products limit the realization of strengthening potential from the formulation source.
[0006] To address this issue, this application provides a high-stress, slow-relaxation chemically strengthened ultrathin glass and its preparation method, which solves the problems of low surface compressive stress and rapid stress decay with increasing strengthening time in one-time-formed ultrathin glass after chemical strengthening. By using a specific glass formulation and reasonable control of the annealing cooling rate, the strengthened ultrathin glass can have both high CS (≥1000MPa) and a gentle stress decay curve.
[0007] Specifically, the technical solution provided in this application includes: (1) A method for preparing ultrathin glass, the method comprising: The glass composition raw materials are melted to obtain a molten liquid; The molten liquid is molded in one step and then subjected to a first annealing to room temperature to obtain an intermediate product; The intermediate product is heated and subjected to a second annealing to room temperature to obtain ultrathin glass; The heating endpoint temperature is 450℃~600℃, the heating holding time is 1h~10h, and the cooling rate of the second annealing is 10℃ / h~300℃ / h.
[0008] This application achieves full relaxation of the glass structure and significantly improves the density of the network structure by reheating and slowly cooling the intermediate product after one-time molding. This results in ultra-thin glass with high surface compressive stress and a moderate stress decay curve after chemical strengthening, and good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0009] In some embodiments of this application, the final heating temperature, the holding time during heating, the cooling rate of the second annealing, and the final temperature of the second annealing can be obtained by the following formula: Where CS is the target compressive stress of the target chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, and t is the time in h.
[0010] Furthermore, the final heating temperature, the holding time during heating, the cooling rate of the second annealing, and the final temperature of the second annealing can be obtained by the following formula: , t eff =t h +t eq , , Where CS is the target compressive stress of the chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, th is the heating holding time in h, and T end γ is the endpoint temperature of the second annealing in °C, v is the cooling rate of the second annealing in °C / h, γ is the equivalent temperature constant related to the relaxation activation energy in K, and t is the integral variable in h. Among them, A, α, β, γ are determined using a global nonlinear regression method.
[0011] In this application, the above formula can guide the preparation of ultrathin glass, enabling the rapid and accurate production of ultrathin glass suitable for preparing chemically strengthened ultrathin glass that meets the target compressive stress.
[0012] In some embodiments of this application, the composition of the ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0013] In this application, by ensuring that each component in the ultrathin glass meets specific ranges, and in conjunction with the aforementioned preparation method, the ultrathin glass obtained after chemical strengthening exhibits high surface compressive stress and a moderate stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0014] It should be noted that in this application, the composition of the glass is expressed as the mass percentage of oxides. [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the glass, respectively. For example, depending on the object, it may refer to the mass percentage in the ultrathin glass, or the mass percentage in the composition of the tensile stress layer or center of the chemically strengthened ultrathin glass, or the mass percentage in the substrate glass, or the mass percentage in the glass composition.
[0015] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.80 ≤ [MgO] / [ZrO2] ≤ 2.00.
[0016] In some embodiments of this application, the composition of the ultrathin glass satisfies: 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) ≤2.00.
[0017] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50.
[0018] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35.
[0019] In some embodiments of this application, the composition of the ultrathin glass satisfies: [B2O3]+[CaO]+[K2O]≤3.00%.
[0020] In this application, by enabling the components of a specific content in the ultrathin glass to exert synergistic effects, combined with the aforementioned preparation method, the ultrathin glass obtained after chemical strengthening has a high surface compressive stress and a mild stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0021] (2) An ultra-thin glass, wherein the ultra-thin glass is prepared by reheating an intermediate product that has been formed in one step and subjected to a first annealing to room temperature to 450°C to 600°C and holding it at that temperature for 1h to 10h, and then subjecting it to a second annealing to room temperature at a cooling rate of 10°C / h to 300°C / h. The composition of the ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0022] This application achieves this by ensuring that each component in the ultrathin glass meets specific ranges and by employing a specific preparation method, thereby enabling the glass structure to fully relax and significantly improving the density of the network structure. This results in ultrathin glass prepared by this method exhibiting high surface compressive stress and a moderate stress decay curve after chemical strengthening, and also showing good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high-temperature or long-term use.
[0023] In some embodiments of this application, the ultrathin glass contains, by mass percentage of oxides, The SiO2 content is 53.50%~60.00%; and / or, The Al2O3 content is 17.50%~24.50%; and / or, The Na₂O content is 15.50%~18.50%; and / or, The K2O content is 0~1.20%; and / or, The MgO content is 1.50%~3.00%; and / or, The ZrO2 content is 1.50%~2.00%; and / or, The Y2O3 content is 0~1.00%; and / or, The B2O3 content is 0~1.00%; and / or, The CaO content is 0~0.80%; and / or, The P2O5 content is 0~1.00%.
[0024] In this application, by ensuring that each component in the ultrathin glass meets specific ranges, the resulting ultrathin glass exhibits high surface compressive stress and a moderate stress decay curve after chemical strengthening, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0025] It should be noted that in this application, the composition of the glass is expressed as the mass percentage of oxides. [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the glass, respectively. For example, depending on the object, it may refer to the mass percentage in the ultrathin glass, or the mass percentage in the composition of the tensile stress layer or center of the chemically strengthened ultrathin glass, or the mass percentage in the substrate glass, or the mass percentage in the glass composition.
[0026] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.80 ≤ [MgO] / [ZrO2] ≤ 2.00.
[0027] In some embodiments of this application, the composition of the ultrathin glass satisfies: 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) ≤2.00.
[0028] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50.
[0029] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35.
[0030] In some embodiments of this application, the composition of the ultrathin glass satisfies: [B2O3]+[CaO]+[K2O]≤3.00%.
[0031] In this application, by enabling the components in a specific amount in the ultrathin glass to exert a synergistic effect, the ultrathin glass produced after chemical strengthening has a high surface compressive stress and a mild stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0032] In some embodiments of this application, the thickness of the ultrathin glass is 0.03 mm to 0.5 mm.
[0033] In this application, the thickness of the ultra-thin glass is controlled to be 0.03mm~0.5mm, which can better meet the requirements of the equipment to be thinner and lighter.
[0034] In some embodiments of this application, the arithmetic mean roughness Ra of the surface of the ultrathin glass after one-time molding is ≤1nm, preferably ≤0.7nm.
[0035] In some embodiments of this application, the ultrathin glass is transparent in the visible light range. Preferably, when the thickness of the ultrathin glass is 0.03 mm to 0.5 mm, the transmittance of the ultrathin glass at a wavelength of 550 nm is ≥91.50%.
[0036] In some embodiments of this application, when the thickness of the ultrathin glass is 0.03mm to 0.5mm, the haze of the ultrathin glass is ≤0.2%.
[0037] In this application, the ultrathin glass exhibits high visible light transmittance and low haze, indicating good light transmission and transparency. Using this ultrathin glass, chemically strengthened ultrathin glass with similar high transmittance and low haze can be prepared.
[0038] It should be noted that the glass performance requirements provided in this application, such as optical performance requirements, stress performance requirements, and strength performance requirements, are not limited to a specific thickness. The thickness of 0.03mm to 0.5mm used in the specific embodiments is only for simplification and is not a limitation on the scope of protection.
[0039] (3) A chemically strengthened ultrathin glass, wherein the chemically strengthened ultrathin glass is obtained by chemically strengthening ultrathin glass, wherein the ultrathin glass is obtained by reheating an intermediate product that has been formed in one step and annealed to room temperature to 450°C~600°C and holding it at that temperature for 1h~10h, and then annealing it to room temperature at a cooling rate of 10°C / h~300°C / h. The chemically strengthened ultrathin glass includes a compressive stress layer and a tensile stress layer; The composition of the chemically strengthened ultrathin glass tensile stress layer or the composition of the center of the chemically strengthened ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0040] This application achieves this by ensuring that each component in the tensile stress layer or center of the chemically strengthened ultrathin glass meets specific ranges and by employing a specific preparation method. This allows the glass structure to fully relax and significantly improves the density of the network structure, resulting in the chemically strengthened ultrathin glass having high surface compressive stress and a gentle stress decay curve. Furthermore, it exhibits a good surface compressive stress residual rate under high-temperature conditions, which is beneficial for the product to maintain high strength during high-temperature or long-term use.
[0041] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass, based on the mass percentage of oxides, The SiO2 content is 53.50%~60.00%; and / or, The Al2O3 content is 17.50%~24.50%; and / or, The Na₂O content is 15.50%~18.50%; and / or, The K2O content is 0~1.20%; and / or, The MgO content is 1.50%~3.00%; and / or, The ZrO2 content is 1.50%~2.00%; and / or, The Y2O3 content is 0~1.00%; and / or, The B2O3 content is 0~1.00%; and / or, The CaO content is 0~0.80%; and / or, The P2O5 content is 0~1.00%.
[0042] In this application, by ensuring that each component in the tensile stress layer or center of the chemically strengthened ultrathin glass meets specific ranges, the chemically strengthened ultrathin glass has high surface compressive stress and a gentle stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0043] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies: 0.80≤[MgO] / [ZrO2] ≤2.00, preferably, 0.90≤[MgO] / [ZrO2] ≤1.90.
[0044] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies: 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O])≤2.00.
[0045] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies: 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50.
[0046] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies: 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35, preferably, 0.15≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35.
[0047] In some embodiments of this application, the composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies: [B2O3]+[CaO]+[K2O]≤3.00%.
[0048] In this application, by enabling the components in a specific amount in the tensile stress layer or center of the chemically strengthened ultrathin glass to exert a synergistic effect, the chemically strengthened ultrathin glass has a high surface compressive stress and a mild stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0049] In some embodiments of this application, the thickness of the chemically strengthened ultrathin glass is 0.03 mm to 0.5 mm.
[0050] In this application, the thickness of the chemically strengthened ultrathin glass is controlled to be 0.03mm~0.5mm, which can better meet the requirements for the thinness and lightness of the equipment.
[0051] In some embodiments of this application, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has an average CS of ≥1000 MPa, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass. Preferably, the chemically strengthened ultrathin glass has an average CS of 1020 MPa to 1250 MPa.
[0052] In some embodiments of this application, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has a DOL_0 of ≥5.0 μm, where DOL_0 is the compressive stress layer depth. Preferably, the chemically strengthened ultrathin glass has a DOL_0 of 5.0 μm to 11.0 μm.
[0053] In this application, by making the chemically strengthened ultrathin glass meet a suitable stress structure, it is beneficial to obtain chemically strengthened ultrathin glass products with a high stress level, thereby making full use of the stress structure to improve mechanical strength performance and ensuring that the chemically strengthened ultrathin glass meets excellent damage resistance performance.
[0054] In some embodiments of this application, when the chemically strengthened glass is in pure KNO3 molten salt at 380°C and the strengthening time is extended from 20 min to 60 min, the average CS decrease rate of the chemically strengthened ultrathin glass is ≤ 2.5%, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass, preferably ≤ 2.0%.
[0055] In some embodiments of this application, when the chemically strengthened ultrathin glass is strengthened in pure KNO3 molten salt at 380°C, and the strengthening time is extended from 20 min to 60 min, the DOL of the glass increases by ≥ 2.0 μm, where DOL_0 is the compressive stress layer depth.
[0056] In some embodiments of this application, the average CS of the chemically strengthened ultrathin glass has a residual rate of ≥88% at 300℃ / 1h, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass.
[0057] (4) A cover glass comprising an ultrathin glass produced by the method of any embodiment of the first aspect, an ultrathin glass of any embodiment of the second aspect, or a chemically strengthened ultrathin glass of any embodiment of the third aspect. The cover glass may be a display screen cover, a sensor module cover, or a thin-film battery cover for an electronic device.
[0058] (5) An electronic device comprising ultrathin glass produced by the method of any embodiment of the first aspect, ultrathin glass of any embodiment of the second aspect, or chemically strengthened ultrathin glass of any embodiment of the third aspect.
[0059] In some embodiments of this application, the electronic device includes a housing assembled on the outside of the electronic device, the housing including ultrathin glass made by the method of any embodiment of the first aspect, ultrathin glass of any embodiment of the second aspect, or chemically strengthened ultrathin glass of any embodiment of the third aspect.
[0060] In some embodiments of this application, the housing includes a display screen cover assembled on the front side of the electronic device, the display screen cover including ultra-thin glass made by the method of any embodiment of the first aspect, ultra-thin glass of any embodiment of the second aspect, or chemically strengthened ultra-thin glass of any embodiment of the third aspect.
[0061] In some embodiments of this application, the electronic device includes a foldable electronic device, a display, a sensor, a semiconductor package, or a thin-film battery. Preferably, the sensor includes a fragile sensor, a fingerprint sensor, or an image sensor. Preferably, ultra-thin glass or chemically strengthened ultra-thin glass is used in the substrate or cover of the electronic device.
[0062] In some embodiments, the housing may be partially or entirely made of ultrathin glass or chemically strengthened ultrathin glass. At least one main surface of the ultrathin glass or chemically strengthened ultrathin glass may include a coating or laminate of organic or inorganic materials.
[0063] (6) A glass device comprising an ultrathin glass obtained by the method of any embodiment of the first aspect, an ultrathin glass of any embodiment of the second aspect, or a chemically strengthened ultrathin glass of any embodiment of the third aspect.
[0064] One or more of the technical solutions provided in this application have the following advantages compared with the prior art: This application provides an ultrathin glass, a high-stress slow-relaxation chemically strengthened ultrathin glass, and a method for preparing the same. It addresses the problems of low surface compressive stress and rapid stress decay with increasing strengthening time in one-piece molded ultrathin glass after chemical strengthening. Through a specific glass formulation and reasonable control of the annealing cooling rate, the strengthened ultrathin glass exhibits both high compressive stress (CS) (≥1000MPa) and a gentle stress decay curve. The ultrathin glass or chemically strengthened ultrathin glass provided by this application can meet the application requirements in fields such as mobile phone cover plates. Attached Figure Description
[0065] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0066] Figure 1 A schematic flowchart illustrating the method for preparing ultrathin glass according to an embodiment of this application; Figure 2 This is a schematic diagram of the front structure of an electronic device provided in an embodiment of this application; Figure 3 A schematic diagram of the rear structure of an electronic device provided in an embodiment of this application; Reference numerals: 11-Display cover; 12-Back cover; 13-Camera protective cover. Detailed Implementation
[0067] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of this application. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0068] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the ranges, the endpoint values of the ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms “optionally,” “optionally,” or similar expressions mean that they may or may not be included (or may or may not be present). The term “and / or” as used herein is inclusive; for example, “A and / or B” means only A, or only B, or both A and B. The term “about” in this document indicates that reasonable deviations are permissible.
[0069] It should be noted that the performance requirements of the glass (such as ultra-thin glass or chemically strengthened ultra-thin glass) provided in this application, such as optical performance requirements, stress performance requirements, and strength performance requirements, are not limited to a specific thickness. The 0.5mm thickness used in the specific embodiment for testing is only for simplification and is not a limitation on the scope of protection.
[0070] Terminology and testing methods: In this application, ultrathin glass refers to glass material with a thickness of 0.03mm to 0.5mm.
[0071] In this application, chemically strengthened ultrathin glass refers to a solid material obtained by chemically strengthening ultrathin glass.
[0072] It should be understood that during chemical strengthening, after the ultrathin glass is placed in a molten salt bath (or salt bath) for ion exchange, a compressive stress zone (or compressive stress layer) is formed on the surface of the ultrathin glass, while a tensile stress zone (or tensile stress layer) is formed inside the ultrathin glass. In other words, after chemical strengthening, ultrathin glass containing both compressive and tensile stress layers is produced.
[0073] In this application, the substrate glass, also known as the base glass, refers to glass that has not undergone nucleation treatment, crystallization treatment, or strengthening treatment.
[0074] In this application, the composition at the center of the chemically strengthened ultrathin glass refers to the composition at or near the center of the depth or thickness of the chemically strengthened ultrathin glass, that is, the composition of the region in the chemically strengthened ultrathin glass where ion exchange has not occurred. It should be understood that, in this application, the composition at the center of the chemically strengthened ultrathin glass or the composition of the tensile stress layer of the chemically strengthened ultrathin glass is the same as or substantially the same as the composition of unstrengthened ultrathin glass.
[0075] In this application, the visible light wavelength range refers to 360nm~740nm.
[0076] In this application, the main surface refers to the surface with the largest surface area, such as the upper or lower surface of a horizontally placed ultrathin glass or chemically strengthened ultrathin glass sheet.
[0077] In this application, the thickness of the ultrathin glass or chemically strengthened ultrathin glass is obtained by micrometer measurement.
[0078] In this application, the dimensions of the ultra-thin glass or chemically strengthened ultra-thin glass sheet are obtained by testing with a two-dimensional measuring machine (instrument model: MiyuMY-YXCL-4030).
[0079] In this application, when light of a certain wavelength is irradiated onto the main surface of ultrathin glass or chemically strengthened ultrathin glass, the light will be reflected, absorbed, and transmitted. The ratio of the intensity of the transmitted portion to the intensity of the incident light is the transmittance.
[0080] In this application, CS refers to the surface compressive stress of chemically strengthened ultrathin glass, measured in MPa, and obtained by testing with an FSM-9000H provided by Shenzhen Tianye Instruments Co., Ltd. Average CS refers to the average value after multiple measurements of surface compressive stress, for example, three measurements.
[0081] In this application, DOL_0 refers to the depth of the compressive stress layer formed on the surface of chemically strengthened ultrathin glass through an ion exchange process, which was obtained by testing with an FSM-9000H provided by Shenzhen Tianye Instruments Co., Ltd.
[0082] In this application, the aforementioned stress performance testing method is as follows: the CS and DOL_0 of the chemically strengthened ultrathin glass are tested using an ASM365, with the refractive index set to 1.51 and the photoelastic coefficient set to 28.6.
[0083] In this application, the component content testing was conducted as follows: lithium oxide and boron oxide were analyzed according to the People's Republic of China National Standard GB / T 1549-2008 "Chemical Analysis Methods for Fiber Glass". Other oxides were determined using X-ray fluorescence spectrometry (XRF). The testing equipment was a Thermo Fisher Scientific ARLPERFORM'X wavelength dispersive X-ray fluorescence spectrometer with a 40 kW tube voltage, 60 mA current, a 0.15 collimator, LiF200 crystal, an FPC detector, a 29 mm circle testing range, and a sample size of 50*50 mm*0.5 mm. The fluorescence intensity was calculated using a standard curve method, and the lithium oxide and boron oxide test results were normalized to obtain the molar percentage content of each analyte.
[0084] In this application, the surface roughness Ra of the glass under test is measured using a UKC ER-230 white light interferometer.
[0085] The applicant found that the cooling process of one-piece molded glass is usually rapid cooling (air cooling or wind cooling), the glass structure is frozen at a high hypothetical temperature state, the network is loose, the compressive stress formed after ion exchange is difficult to maintain, and the stress gradient is steep in the depth direction.
[0086] Existing technologies attempt to improve the situation by adjusting the strengthening process (such as extending the strengthening time and increasing the molten salt temperature), but the effects are limited and often lead to an excessively deep stress layer and a decrease in surface compressive stress. More importantly, glass formulations suitable for one-time molding and capable of achieving high stress are still imperfect, and existing products limit the realization of strengthening potential from the formulation source.
[0087] To address this issue, this application provides a high-stress, slow-relaxation chemically strengthened ultrathin glass and its preparation method, which solves the problems of low surface compressive stress and rapid stress decay with increasing strengthening time in one-time-formed ultrathin glass after chemical strengthening. By using a specific glass formulation and reasonable control of the annealing cooling rate, the strengthened ultrathin glass can have both high CS (≥1000MPa) and a gentle stress decay curve.
[0088] In some embodiments of this application, a glass composition is provided, comprising, by mass percentage of oxides: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0089] It should be understood that the glass composition in this application can be used to prepare a substrate glass by existing methods, the composition of which is substantially the same as that of the glass composition, except for clarifiers and unavoidable impurities.
[0090] In some embodiments of this application, a substrate glass is provided, the composition of which, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0091] It should be understood that the substrate glass in this application meets a specific ultra-thin thickness, that is, it is an ultra-thin glass, and the composition of the ultra-thin glass is basically the same as that of the substrate glass.
[0092] In some embodiments of this application, an ultrathin glass is provided, wherein the composition of the ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0093] This application achieves the desired results by ensuring that each component in the ultrathin glass meets specific ranges, combined with the aforementioned preparation method. This results in an ultrathin glass that exhibits high surface compressive stress and a moderate stress decay curve after chemical strengthening, and also has a good surface compressive stress residual rate under high temperature conditions. This is beneficial for the product to maintain high strength during high-temperature or long-term use.
[0094] Similarly, it should be understood that the chemically strengthened ultrathin glass in this application is obtained by processing ultrathin glass through processing including chemical strengthening. Unless excessive ion exchange treatment is performed, the composition of the portion of the chemically strengthened ultrathin glass deeper than the compressive stress layer (e.g., the center of the chemically strengthened ultrathin glass or the tensile stress layer of the chemically strengthened ultrathin glass) is the same as or substantially the same as the composition of the ultrathin glass. That is, in terms of the molar percentage of oxides, the composition of the center of the chemically strengthened ultrathin glass or the composition of the tensile stress layer of the chemically strengthened ultrathin glass where ion exchange is substantially not performed is the same as or substantially the same as the composition of the ultrathin glass.
[0095] In some embodiments of this application, a chemically strengthened ultrathin glass is provided, wherein the composition of the tensile stress layer of the chemically strengthened ultrathin glass or the composition of the center of the chemically strengthened ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
[0096] It is understood that the measurement method of the composition of the glass composition, the composition of the substrate glass, the composition of the ultrathin glass, or the composition at the center of the chemically strengthened ultrathin glass can be converted by means of conversion. For example, the measurement method of the above-mentioned mass percentage of oxides can be converted into molar percentage of oxides.
[0097] In this application, SiO2 is the network forging body of the glass, forming a silicon-oxygen tetrahedral framework that provides mechanical strength, chemical stability, and thermal stability. An appropriate SiO2 content ensures sufficient network connectivity while providing open channels for ion exchange. If SiO2 is too low, the network structure becomes too loose, reducing chemical stability and making crystallization more likely. If SiO2 is too high, it significantly increases melt viscosity, deteriorating melting and forming performance.
[0098] In some embodiments of this application, the SiO2 content in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass, based on the molar percentage of oxides, is 53.00% to 61.00%, preferably 53.50% to 60.00%.
[0099] In some embodiments of this application, the SiO2 content, in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, can be 53.00%, 53.50%, 54.00%, 54.50%, 55.00%, 55.50%, 56.00%, 56.50%, 57.00%, 57.50%, 58.00%, 58.50%, 59.00%, 59.50%, 60.00%, 60.50%, 61.00%, 59.90%, 57.90%, or 58.70% by molar percentage of oxides, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0100] In this application, Al2O3 is mainly used in glass to construct and reinforce the glass network framework. Simultaneously, the ion exchange rate can be controlled by adjusting the size of the spaces available for ion exchange within the glass network. If the Al2O3 content is too low, there are insufficient ion exchange sites, resulting in low ion exchange capacity and limited improvement in CS (colour density). Furthermore, the network rigidity is insufficient, leading to rapid stress relaxation and low high-temperature residual rate. If the Al2O3 content is too high, the melt viscosity increases sharply, making clarification difficult. Additionally, corundum crystals (Al2O3) easily precipitate at low temperatures, disrupting glass homogeneity, increasing surface defects after strengthening, and potentially causing spontaneous cracking.
[0101] In some embodiments of this application, the content of Al2O3 in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass, based on the molar percentage of oxides, is 17.00% to 25.00%, preferably 17.50% to 24.50%.
[0102] In some embodiments of this application, the content of Al2O3 in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, based on the molar percentage of oxides, can be 17.00%, 17.50%, 18.00%, 18.50%, 19.00%, 19.50%, 20.00%, 20.50%, 21.00%, 21.50%, 22.00%, 22.50%, 23.00%, 23.50%, 24.00%, 24.50%, 25.00%, 17.80%, 19.80%, 24.10%, or 21.10%, or can be a value within a range of values defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application can be obtained. It should be understood that, in specific implementations, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass or chemically strengthened ultrathin glass with the desired performance of this application can be obtained.
[0103] In this application, Na₂O, as a network exooxide, provides free oxygen, increasing the oxygen-silicon ratio in the glass structure, thereby effectively regulating the glass viscosity and promoting the melting and refining processes. Simultaneously, it can also enhance the Na content in the glass. + –K + Ion exchange helps to achieve higher surface compressive stress (CS). If Na₂O is too low, Na can be exchanged. + Insufficient quantity results in weak ion exchange driving force, making it impossible to achieve high stress. Simultaneously, excessively high melting temperature increases energy consumption. If Na₂O is too high, the network undergoes excessive depolymerization, leading to a loose structure, poor chemical stability, and an excessively high coefficient of thermal expansion, resulting in severe glass warping after strengthening. Furthermore, K... + The stress relaxes rapidly after the exchange.
[0104] In some embodiments of this application, the content of Na2O in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass, based on the molar percentage of oxides, is 15.00% to 20.00%, preferably 15.50% to 18.50%.
[0105] In some embodiments of this application, the Na₂O content, based on the molar percentage of oxides, in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 15.00%, 15.20%, 15.40%, 15.60%, 15.80%, 16.00%, 16.20%, 16.40%, 16.60%, 16.80%, 17.00%, 17.20%, 17.40%, 17.6%. The values can be 0%, 17.80%, 18.00%, 18.20%, 18.40%, 18.60%, 18.80%, 19.00%, 19.20%, 19.40%, 19.60%, 19.80%, 20.00%, 18.10%, or 15.50%, or any value within a range defined by any two of the above specific values as endpoints, as long as the desired performance of the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass of this application can be obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the desired performance of the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass of this application can be obtained.
[0106] In this application, K2O is an outer oxide of the glass network and is an optional component. A small amount of K2O can flux, adjust the coefficient of thermal expansion, and produce a mixed alkali effect, optimizing the ion diffusion rate. However, the content must be strictly controlled because K2O... + A large radius and low electric field strength, if excessive, will reduce the network rigidity. If K2O is excessive, a large amount of K... + Occupying network gaps and weakening network connections; during chemical strengthening, high K within the glass + It will weaken K + -Na + The concentration gradient reduces the exchange driving force, decreases CS, and exacerbates stress relaxation. Therefore, this application limits K2O to ≤ 1.2%.
[0107] In some embodiments of this application, the K2O content in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass is 0 to 1.50%, preferably 0 to 1.20%, based on the molar percentage of oxides.
[0108] In some embodiments of this application, the K2O content, measured by molar percentage of oxides, in the center of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, or in the tensile stress layer, can be 0, 0.20%, 0.40%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.50%, or 0.50%, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0109] In this application, MgO is a mandatory component due to its high electric field strength, which enables network accumulation and increases strain point and hardness. An appropriate amount of MgO promotes structural relaxation of the glass during annealing, lowers the hypothetical temperature, and helps achieve slow stress relaxation. Insufficient MgO results in insufficient accumulation, decreased overall network rigidity, reduced stress coefficient (CS), and increased stress decay rate. Excessive MgO leads to easy crystallization of the glass (e.g., magnesium olivine, enstatite), increased melt surface tension, and more striation defects. Furthermore, excessive MgO in the later stages of ion exchange... 2+ May hinder K + The spread leads to DOL abnormalities.
[0110] In some embodiments of this application, the content of MgO in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass is 0.50% to 3.00%, preferably 1.50% to 3.00%, based on the molar percentage of oxides.
[0111] In some embodiments of this application, the MgO content, in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, can be 0.50%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, 2.00%, 2.20%, 2.40%, 2.60%, 2.80%, 3.00%, 2.70%, 2.30%, or 1.90% by molar percentage of oxides, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0112] In this application, ZrO2 is an intermediate oxide in glass formation. Appropriate addition can improve chemical stability, hardness, and scratch / drop resistance. Its high charge and strong field strength cationic properties have an accumulation effect on the glass structure, and appropriate addition can enhance strengthening stress. If ZrO2 is insufficient, the network rigidity is insufficient, the elastic modulus is low, the CS generated under the same exchange amount is reduced more, and stress relaxation at high temperatures is exacerbated. If ZrO2 is excessive, the glass is difficult to melt, easily forming zircon crystals, resulting in poor glass homogeneity, excessively high melt viscosity, and difficulty in resolving. Simultaneously, excessive ZrO2 content narrows the ion exchange channels, reducing DOL (Density of Lithium Oxide).
[0113] In some embodiments of this application, the ZrO2 content in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass is 0.50% to 2.50%, preferably 1.50% to 2.00%, based on the molar percentage of oxides.
[0114] In some embodiments of this application, the ZrO2 content, in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, can be 0.50%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, 2.00%, 2.10%, 2.20%, 2.30%, 2.40%, or 2.50% by molar percentage of oxides, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0115] In this application, Y2O3 is used as an external oxide of the network and is an optional component. An appropriate amount of Y2O3 can improve hardness and surface hardness (CS) after strengthening, but an excessive amount can easily lead to crystallization.
[0116] In some embodiments of this application, the content of Y2O3 in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass, based on the molar percentage of oxides, is 0 to 2.00%, preferably 0 to 1.00%.
[0117] In some embodiments of this application, the content of Y₂O₃ in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, based on the molar percentage of oxides, can be 0, 0.20%, 0.40%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, or 2.00%, or a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0118] In this application, B2O3 is an optional component as a glass network forger. Trace amounts of B2O3 can reduce high-temperature viscosity and improve melting. However, excessive B2O3 will exist in the form of [BO3]trigonometric structures, disrupting network continuity, causing "boron anomalies," and reducing chemical stability and strengthening properties.
[0119] In some embodiments of this application, the content of B2O3 in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass, based on the molar percentage of oxides, is 0 to 2.00%, preferably 0 to 1.00%.
[0120] In some embodiments of this application, the content of B2O3, in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, can be 0, 0.20%, 0.40%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, or 2.00% by molar percentage of oxides, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0121] In this application, CaO, as an oxide in the network structure, is an optional component. An appropriate amount of CaO can adjust the viscosity of the molten glass and improve the temperature of the forming zone, but excessive CaO will hinder the absorption of Na+. + -K + Switching and reducing network rigidity.
[0122] In some embodiments of this application, the content of CaO in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass is 0 to 1.00%, preferably 0 to 0.80%, based on the molar percentage of oxides.
[0123] In some embodiments of this application, the CaO content, in terms of the molar percentage of oxides, at the center of the glass composition, the substrate glass, the ultrathin glass, or the chemically strengthened ultrathin glass, or in the tensile stress layer, can be 0, 0.20%, 0.40%, 0.60%, 0.80%, or 1.00%, or a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0124] In this application, P2O5 is an optional component as a glass network forming agent. An appropriate amount of P2O5 can promote the ion exchange rate, but an excessive amount will lead to phase separation.
[0125] In some embodiments of this application, the content of P2O5 in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass or chemically strengthened ultrathin glass is 0 to 1.00% by molar percentage of oxides.
[0126] In some embodiments of this application, the P2O5 content, in terms of molar percentage of oxides, at the center of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass, or in the tensile stress layer, can be 0, 0.20%, 0.40%, 0.60%, 0.80%, or 1.00%, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0127] In this application, by ensuring that each component in the ultrathin glass meets specific ranges, the resulting ultrathin glass exhibits high surface compressive stress and a moderate stress decay curve after chemical strengthening, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0128] It should be noted that in this application, the composition of the glass is expressed as the mass percentage of oxides. [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the glass, respectively. For example, depending on the object, it may refer to the mass percentage in the ultrathin glass, or the mass percentage in the composition of the tensile stress layer or center of the chemically strengthened ultrathin glass, or the mass percentage in the substrate glass, or the mass percentage in the glass composition.
[0129] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.8 ≤ [MgO] / [ZrO2] ≤ 2. [MgO] / [ZrO2] represents the glass network stiffness-relaxation equilibrium index. MgO and ZrO2 are two components that significantly affect the network structure and ion exchange behavior. Through extensive experiments, the applicant has discovered that the mass ratio of MgO to ZrO2 (MgO / ZrO2) is a key characteristic parameter determining whether the glass can achieve high surface compressive stress (CS) and suppress stress relaxation after offline slow cooling annealing. When the ratio is too low (<0.9): the glass network stiffness is too high, the network gaps become narrower, and K... + The diffusion resistance during the exchange process increases significantly, leading to a decrease in the peak surface compressive stress. When the ratio is too high (>2), the ZrO2 content is relatively insufficient, the network rigidity decreases, and it remains relatively porous after annealing, resulting in a weakened K2. + Easy migration leads to low CS and rapid decay. In this application, the content relationship between MgO and ZrO2 preferably meets this requirement.
[0130] In some embodiments, the value of the relationship [MgO] / [ZrO2] in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0131] In some embodiments of this application, the composition of the ultrathin glass satisfies: 1.4 ≤ ([Al2O3] + 1.5 × [MgO] + 2 × [ZrO2]) / ([Na2O] + 0.5 [K2O]) ≤ 2. ([Al2O3] + 1.5 × [MgO] + 2 × [ZrO2]) / ([Na2O] + 0.5 [K2O]) represents the glass network stiffness index, where the numerator is the network reinforcing components (Al2O3, MgO, ZrO2), and the denominator is the network modifying components (Na2O, K2O). This index reflects the "rigidity / softness" balance of the glass. When this value is less than 1.1, the network is too soft, and the compressive stress generated by ion exchange cannot be effectively stored, making it difficult for the CS (coefficient of performance) to exceed 1100 MPa. When this value is greater than 2.0, the network is too rigid, the ion exchange resistance is large, the DOL becomes shallower, and stress concentration easily leads to increased brittleness. In this application, the content relationship between Al2O3, MgO, ZrO2, Na2O and K2O preferably meets this requirement.
[0132] In some embodiments, the value of the relationship ([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0133] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.3 ≤ ([Al2O3] + [MgO] - 0.4 × [K2O]) / [SiO2] ≤ 0.5. ([Al2O3] + [MgO] - 0.4 × [K2O]) / [SiO2] represents the glass's ability to lower the hypothetical temperature and achieve structural relaxation during annealing. If the ratio is too low (<0.3), Al2O3 + MgO is relatively insufficient, the hypothetical temperature remains high after annealing, and the increase in CS is limited. If the ratio is too high (>0.5), the network is too dense, the initial ion exchange rate is too slow, and crystallization may be induced. In this application, the content relationship between Al2O3, MgO, K2O, and SiO2 preferably meets this requirement.
[0134] In some embodiments, the value of the relationship ([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2] in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 0.3, 0.4, or 0.5, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0135] In some embodiments of this application, the composition of the ultrathin glass satisfies: 0.1 ≤ ([Al2O3] + 2.5 × [ZrO2] - 0.7 × [Na2O]) / [SiO2] ≤ 0.35. ([Al2O3] + 2.5 × [ZrO2] - 0.7 × [Na2O]) / [SiO2] reflects the K... + The degree to which the stress is firmly "anchored" by the network after the exchange. If the ratio is too low (<0.1), there is a relative excess of Na2O or a deficiency of Al2O3+ ZrO2, resulting in insufficient K after the exchange. + Easy to migrate, rapid stress relaxation. If the ratio is too high (>0.35), there are too few exchange sites or the network is too rigid, K + The exchange process is difficult, and the CS content is insufficient. In this application, the content relationship between Al2O3, ZrO2, Na2O, and SiO2 preferably meets this requirement.
[0136] In some embodiments, the value of the relationship ([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2] in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 0.1, 0.2, 0.3, or 0.35, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0137] In some embodiments of this application, the composition of the ultrathin glass satisfies: [B2O3]+[CaO]+[K2O]≤3.00%. [B2O3]+[CaO]+[K2O] represents the upper limit of the total content of the three oxides (B2O3, CaO, and K2O) in the glass that have a clear negative impact on the network structure and ion exchange performance. Its physical significance lies in the fact that these three components "damage" or "occupy" effective glass networks and ion exchange sites; therefore, their total amount must be suppressed to a low level (below 3.00%). When it exceeds 3.00%, a large number of non-bridging oxides and structural defects appear in the glass network, resulting in lower stress after strengthening and a significant reduction in annealing relaxation efficiency, making it difficult to reduce the hypothetical temperature to the ideal level.
[0138] In some embodiments, the value of the relationship [B2O3]+[CaO]+[K2O] in the center or tensile stress layer of the glass composition, substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 0.20%, 0.40%, 0.60%, 0.80%, 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, 2.00%, 2.20%, 2.40%, 2.60%, 2.80%, or 3.00%, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0139] In this application, by enabling the components in a specific amount in the tensile stress layer or center of the chemically strengthened ultrathin glass to exert a synergistic effect, the chemically strengthened ultrathin glass has a high surface compressive stress and a mild stress decay curve, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0140] In some embodiments of this application, the thickness of the substrate glass, ultra-thin glass, or chemically strengthened ultra-thin glass ranges from 0.03 mm to 0.5 mm, preferably from 0.1 mm to 0.4 mm, and more preferably from 0.2 mm to 0.3 mm. In this application, controlling the thickness of the ultra-thin glass to be 0.03 mm to 0.5 mm effectively meets the requirements for thinner and lighter equipment. In some embodiments, the thickness of the substrate glass, ultra-thin glass, or chemically strengthened ultra-thin glass can be 0.03 mm, 0.05 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, or 0.5 mm, or a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultra-thin glass, or chemically strengthened ultra-thin glass with the performance required by this application is obtained. It should be understood that, in specific implementation schemes, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application can be obtained. It should be understood that, during chemical strengthening or ion exchange treatment of ultrathin glass, the overall increase (mass) in the exchange amount of Na-K and / or Li-Na generally does not exceed 1.5% of the total sample mass. Therefore, the expansion effect in the thickness direction is extremely slight, and the thickness can be approximated as essentially unchanged. That is, the thickness change of the ultrathin glass before and after chemical strengthening is very small and can be basically ignored; the thickness of the ultrathin glass is essentially the same as the thickness of the chemically strengthened ultrathin glass it produces.
[0141] In some embodiments of this application, the arithmetic mean roughness Ra of the surface of the ultrathin glass after one-time molding is ≤1 nm, preferably ≤0.7 nm. Exemplarily, the arithmetic mean roughness Ra of the surface of the ultrathin glass after one-time molding can be 1 nm, 0.9 nm, 0.8 nm, 0.7 nm, 0.6 nm, 0.5 nm, 0.4 nm, 0.3 nm, 0.2 nm, or 0.1 nm, or can be a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application can be obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application can be obtained.
[0142] It is understandable that the transmittance of ultrathin glass before and after chemical strengthening is basically the same as that of chemically strengthened ultrathin glass. That is, in this application, by using ultrathin glass with high transmittance, chemical strengthening treatment can be used to obtain chemically strengthened ultrathin glass products with the same excellent transmittance.
[0143] In some embodiments of this application, the ultrathin glass or chemically strengthened ultrathin glass is transparent in the visible light wavelength range. Preferably, when the thickness of the ultrathin glass is 0.03 mm to 0.5 mm, the transmittance of the ultrathin glass at a wavelength of 550 nm is ≥91.50%. Ultrathin glass or chemically strengthened ultrathin glass that meets this transmittance can ensure good light transmission and a good transparency effect. Here, "visible light wavelength range" refers to light with wavelengths of 360 nm to 740 nm.
[0144] In some embodiments, when the thickness is 0.03 mm to 0.5 mm, the transmittance of the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass at a wavelength of 550 nm can be 91.50%, 92.00%, 92.05%, 92.10%, 92.01%, 91.98%, 92.13%, 92.11%, 92.05%, or 91.97%, or a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0145] In some embodiments of this application, when the thickness of the ultrathin glass is 0.03mm to 0.5mm, the haze of the ultrathin glass is ≤0.2%.
[0146] In some embodiments, when the thickness is 0.03mm to 0.5mm, the haze of the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass can be 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%, or a value within a range defined by any two of the above specific values as endpoints, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the substrate glass, ultrathin glass, or chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0147] In this application, the ultrathin glass exhibits high visible light transmittance and low haze, indicating good light transmission and transparency. Using this ultrathin glass, chemically strengthened ultrathin glass with similar high transmittance and low haze can be prepared. It should be noted that the glass performance requirements provided in this application, such as optical performance requirements, stress performance requirements, and strength performance requirements, are not limited to a specific thickness. The 0.03mm~0.5mm thickness used in the specific embodiments is for simplification only and is not a limitation on the scope of protection.
[0148] Having introduced the composition of ultrathin glass, the following section will provide a detailed description of its preparation methods.
[0149] In this application, the preparation process of ultrathin glass mainly includes: one-time forming of substrate glass → first annealing → heating → second annealing → cutting → chemical etching → edge treatment.
[0150] In some embodiments of this application, the composition of the substrate glass used to prepare the ultrathin glass is the same as or substantially the same as the composition of the ultrathin glass, based on the molar percentage of oxides; the specific composition is as described above.
[0151] In this application, the substrate glass can be prepared using existing forming methods, and this application has no limitations on this. For example, the forming method of the substrate glass may include, but is not limited to, narrow-slit drawing, overflow drawing, secondary thinning, casting and rolling, casting and melting, or float glass. Exemplarily, the substrate glass can be obtained by uniformly mixing the components according to the glass composition formula, melting and forming, and then cooling and annealing.
[0152] Exemplarily, raw materials (common industrial raw materials) are prepared according to the formulation ratio of the glass composition, a clarifying agent is added, and then mixed for a period of time to obtain a uniformly mixed raw material mixture. After melting the raw material mixture, it is formed in one step, and then annealed to obtain the substrate glass. In some embodiments of this application, one-step forming includes any one of narrow-slit drawing, overflow drawing, secondary thinning, casting and rolling, casting and melting bricks, and float glass. The narrow-slit drawing method and overflow drawing method are preferred, with a melting temperature of 1350°C to 1700°C, a melting time of 4h to 240h, a drawing speed of 0.1m / min to 15m / min, a forming temperature of 850°C to 1300°C, a first annealing temperature of 850°C to 300°C, and a first annealing treatment time of 0.1min to 2000min.
[0153] In this application, after one-time molding and first annealing to room temperature, the temperature is reheated to 450℃~600℃ and held for 1h~10h, followed by a second annealing to room temperature at a cooling rate of 10℃ / h~300℃ / h.
[0154] In some embodiments of this application, the final heating temperature, the holding time during heating, the cooling rate of the second annealing, and the final temperature of the second annealing can be obtained by the following formula: Where CS is the target compressive stress of the target chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, and t is the time in h.
[0155] Furthermore, the final heating temperature, the holding time during heating, the cooling rate of the second annealing, and the final temperature of the second annealing can be obtained using the following formulas: , t eff =t h +t eq , , Where CS is the target compressive stress of the chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, th is the heating holding time in h, and T end γ is the endpoint temperature of the second annealing in °C, v is the cooling rate of the second annealing in °C / h, γ is the equivalent temperature constant related to the relaxation activation energy in K, and t is the integral variable in h. Among them, A, α, β, γ are determined using a global nonlinear regression method.
[0156] A, α, β, and γ are determined using a global nonlinear regression method. For example, a fixed cooling rate (v = 120℃ / h) can be used, and the formula can be adjusted based on the data in Table 1. Nonlinear regression was performed to initially obtain parameters A, α, and β. Annealing experiments were designed with different annealing temperatures T, holding times th, and cooling rates v. Under the same chemical strengthening conditions (e.g., treatment in pure KNO3 molten salt at 380℃ for 20 min), the surface compressive stress CSexp of each sample was measured, obtaining a complete dataset (Tables 1 and 2). Subsequently, the formulas were analyzed. When performing global nonlinear regression, teq is given by the formula Integrating, we obtain the final fit, which includes all four parameters, including γ. The specific process of global nonlinear regression is as follows: The glass composition used is (SiO2: 59.9, Al2O3: 17.8, Na2O: 16.8, K2O: 1.2, MgO: 2.8, ZrO2: 1.5).
[0157] The chemical strengthening conditions used were: treatment with pure KNO3 molten salt at 380℃ for 20 minutes.
[0158] With the cooling rate data of the second degradation fixed (v=120℃ / h), the measured values of CS under different heating endpoint temperatures T and heating holding times th are shown in Table 1.
[0159] Table 1. Measured values of CS under different heating endpoint temperatures T and heating holding times th.
[0160] A variable cooling rate experiment was designed. The final heating temperature T = 530℃, the heating holding time th = 5h, and the final second annealing temperature Tend = 300℃ were fixed. The cooling rates v (℃ / h) of the second annealing were varied. The measured CS values under different cooling rates of the second annealing are shown in Table 2.
[0161] Table 2. Measured CS values under different cooling rates for the second annealing.
[0162] Global fitting result: Substitute all the above data into the formula In the process, the nonlinear least squares method was used for global fitting, and the optimal parameters were obtained: A=2120MPa, α=0.0344, β=586.4K, γ=6950K.
[0163] Using the above parameters, teq and predicted CS values were calculated for each experimental point, and the results are shown in Tables 3 and 4. All relative deviations were within 1%. The measured CS values were then substituted into the formula. The teff is obtained from the given th, and then the inverse teq value is obtained by subtracting the known th. The teq obtained by integration is completely consistent with the teq inversely derived from the measured CS values, indicating model self-consistency. The relative deviation | |=|CSpred-CSexp| / |CSpred+CSexp|*100%.
[0164] Table 3. Prediction results at a fixed cooling rate (120℃ / h)
[0165] Table 4. Prediction results under varying cooling rates
[0166] It should be noted that for other glass formulations within the scope of this application, those skilled in the art can obtain the corresponding model parameters by following the same method (designing annealing experiments with different T, th, and v, measuring CS, and then performing global nonlinear regression).
[0167] In this application, the cutting process can be as follows: the substrate glass is cut to obtain a sample of a fixed size. This application does not limit the size processing of the substrate glass or ultra-thin glass sample. Preferably, the fixed sample size is 200 mm * 200 mm in length and width, with a thickness of 0.03-0.5 mm and a total thickness variation (TTV) of less than or equal to 5 μm. Here, "TTV" refers to total thickness variance, the difference between the maximum and minimum thickness on the sample, mainly indicating the uniformity of thickness within the same sample.
[0168] In this application, the chemical etching process can be as follows: using a top-spray or immersion chemical etching machine, after etching in the etching solution for a certain period of time, an ultrathin glass sample is obtained. The ultrathin glass can be processed and produced by photomask method, coating method, arc mold fixed etching method, precision liquid flow guided etching method, forward and reverse pulling method, etc. The preferred etching solution is one or more of hydrofluoric acid, sulfuric acid, nitric acid, hydrochloric acid, and ammonium fluoride; the preferred etching temperature is 20℃~50℃; the preferred etching rate is 0.1μm / min~20μm / min; the preferred etching solution is HF (volume fraction 0.6%-0.7%), H2SO4 (volume fraction 0.5%-0.6%), HNO3 (volume fraction 0.4%-0.5%), and the remainder is water. The processing time is 120s, the etching temperature is controlled at 65℃, and the etching rate is 0.2μm / min.
[0169] In this application, the edge treatment process can be as follows: A specific strong acid-resistant ink is coated onto the two main surfaces of an ultra-thin glass sample using a scraper. Then, it is laser-cut to the required size. The cut sample is then placed in an etching tank for chemical etching. The preferred etching time is 1 min to 10 min, and the preferred etching solution is one or more of hydrofluoric acid, sulfuric acid, nitric acid, hydrochloric acid, and ammonium fluoride. The preferred etching temperature is 20℃ to 50℃, and the preferred etching rate is 0.1 μm / min to 10 μm / min. Afterward, the edge-treated sample is placed in an alkaline solution for deinking. The preferred alkaline solution is one or more of NaOH, NaHCO3, and Na2CO3. The preferred deinking temperature is 40℃ to 100℃, and the preferred deinking time is 1 min to 120 min. A preferred deinking process is: 0.5%-1% NaOH (volume fraction), 0.3%-0.5% NaHCO3 (volume fraction), and the remainder is water. The deinking temperature is controlled at 75℃, and the treatment time is 10 min.
[0170] In some embodiments of this application, the chemically strengthened ultrathin glass is obtained by chemically strengthening the aforementioned ultrathin glass. The composition of the center or tensile stress layer of the chemically strengthened ultrathin glass is the same as or substantially the same as the composition of the aforementioned ultrathin glass. The chemically strengthened ultrathin glass includes a compressive stress layer region extending from the surface of the chemically strengthened ultrathin glass to the compression depth, and has tensile stress inside the chemically strengthened ultrathin glass, having a tensile stress layer region.
[0171] In this application, the chemical strengthening treatment, namely the ion exchange method, involves immersing ultrathin glass in a molten salt bath / melted salt bath, allowing alkali metal ions with smaller ionic radii in the ultrathin glass to exchange with alkali metal ions with larger ionic radii in the salt bath. This forms a compressive stress layer on the surface of the ultrathin glass and a tensile stress layer inside it, resulting in chemically strengthened ultrathin glass with superior mechanical properties.
[0172] In some embodiments of this application, the chemical enhancement treatment can be performed using a single-step enhancement method or a multi-step enhancement method. The molten salt bath used for the chemical enhancement treatment is a molten salt bath containing potassium salt. Preferably, in this application, the molten salt bath used for the chemical enhancement treatment can be a pure potassium salt bath, or a mixed salt bath containing potassium and sodium salts, and a certain amount of lithium salt can also be appropriately added to the salt bath. Preferably, the ratio of the enhancement salt bath is: 0-10 wt% sodium nitrate, 1-100 wt% potassium nitrate. Preferably, in this application, the temperature of the salt bath used for the chemical enhancement treatment is 370℃~550℃, more preferably 430℃~500℃. Preferably, in this application, the chemical enhancement treatment time can be 5 min~240 min. The potassium salt can be selected from at least one of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the sodium salt can be selected from at least one of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; the lithium salt can be selected from at least one of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.
[0173] In some embodiments of this application, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has an average CS of ≥1000 MPa, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass. Preferably, the chemically strengthened ultrathin glass has an average CS of 1020 MPa to 1250 MPa. When a blunt or sharp object comes into contact with the chemically strengthened ultrathin glass, the stress structure on the surface of the chemically strengthened ultrathin glass will preferentially offset the impact force it receives. By giving the chemically strengthened ultrathin glass a higher surface stress level, it can offset more energy from drops, compression, impacts, or collisions, thereby helping to ensure its excellent damage resistance, such as excellent resistance to compression and scratches.
[0174] Those skilled in the art will understand that for chemically strengthened ultrathin glass, CS (compressive stress) can significantly improve flexural strength and flexibility. High CS can form a deeper compressive stress layer on the glass surface, effectively inhibiting the propagation of microcracks, thereby greatly improving bending life and reducing the risk of breakage. Simultaneously, high CS can enhance impact and scratch resistance (chemically strengthened ultrathin glass is more sensitive to point impacts and scratches). High CS increases surface hardness, resulting in shallower scratches in daily use and dispersing impact energy, reducing brittle fracture. Furthermore, high CS can reduce thickness dependence (traditional chemically strengthened ultrathin glass requires a thicker design to ensure strength, but this sacrifices flexibility). High CS allows for maintaining excellent mechanical properties at a thinner thickness, thereby achieving higher folding flatness and a smaller bending radius.
[0175] In some embodiments, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the average CS of the chemically strengthened ultrathin glass can be 1000 MPa, 1050 MPa, 1100 MPa, 1150 MPa, 1200 MPa, 1250 MPa, 1300 MPa, 1350 MPa, 1400 MPa, 1450 MPa, 1500 MPa, 1550 MPa, 1600 MPa, 1650 MPa, 1700 MPa, 1750 MPa, 1800 MPa, 1023 MPa, 1035 MPa, 1021 MPa, 1067 MPa, 1075 MPa, 1053 MPa, 1071 MPa, 1080 MPa, 1061 MPa, 1210 MPa, 1205 MPa, 1185 MPa, 1141 MPa, 1137 MPa, etc. The pressure can be 1132 MPa, 1089 MPa, 1095 MPa, 1081 MPa, 1147 MPa, 1151 MPa, 1153 MPa, 1142 MPa, or 1149 MPa, or any value within a range defined by any two of the above specific values as endpoints, as long as it yields the chemically strengthened ultrathin glass with the performance required by this application. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other range, as long as it yields the chemically strengthened ultrathin glass with the performance required by this application.
[0176] In some embodiments of this application, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has a DOL_0 of ≥5.0 μm, where DOL_0 is the compressive stress layer depth. Preferably, the chemically strengthened ultrathin glass has a DOL_0 of 5.0 μm to 11.0 μm.
[0177] In some embodiments, when the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the compressive stress layer depth DOL_0 of the chemically strengthened ultrathin glass can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 6.12 μm, 8.43 μm, 10.55 μm, 6.09 μm, 8.61 μm, 10.71 μm, 5.82 μm, 8.0 μm, etc. The thickness can be 5 μm, 9.87 μm, 5.91 μm, 8.31 μm, 9.98 μm, 5.58 μm, 7.98 μm, 9.77 μm, 5.81 μm, 8.28 μm, 10.09 μm, 5.27 μm, 7.41 μm, 9.49 μm, 5.79 μm, 8.37 μm, or 10.12 μm, or any value within a range defined by any two of the above specific values as endpoints, as long as it yields the chemically strengthened ultrathin glass with the desired performance of this application. It should be understood that in specific embodiments, any of the above ranges can be combined with any other range, as long as it yields the chemically strengthened ultrathin glass with the desired performance of this application.
[0178] In this application, by making the chemically strengthened ultrathin glass meet a suitable stress structure, it is beneficial to obtain chemically strengthened ultrathin glass products with a high stress level, thereby making full use of the stress structure to improve mechanical strength performance and ensuring that the chemically strengthened ultrathin glass meets excellent damage resistance performance.
[0179] In some embodiments of this application, when the chemically strengthened ultrathin glass is subjected to strengthening in pure KNO3 molten salt at 380°C, and the strengthening time is extended from 20 min to 60 min, the average CS decrease rate of the chemically strengthened ultrathin glass is ≤ 2.5%, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass, preferably ≤ 2.0%. The average CS decrease rate of the chemically strengthened ultrathin glass is calculated as: (maximum CS value - minimum CS value) / maximum CS value × 100%.
[0180] In some embodiments, when strengthening in pure KNO3 molten salt at 380°C, and when the strengthening time is extended from 20 min to 60 min, the average CS reduction rate of the chemically strengthened ultrathin glass can be 2.5%, 2.0%, 1.5%, 1.0%, 0.5%, or 0, or a value within a range defined by any two of the above specific values as endpoints, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other range, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0181] In some embodiments of this application, when the chemically strengthened ultrathin glass is strengthened in pure KNO3 molten salt at 380°C, and the strengthening time is extended from 20 min to 60 min, the DOL of the glass increases by ≥ 2.0 μm, where DOL_0 is the compressive stress layer depth.
[0182] In some embodiments, when strengthening in pure KNO3 molten salt at 380°C, and when the strengthening time is extended from 20 min to 60 min, the increase in DOL of the chemically strengthened ultrathin glass can be 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, or 10 μm, or a value within a range defined by any two of the above specific values as endpoints, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that in specific embodiments, any of the above ranges can be combined with any other range, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0183] In some embodiments of this application, the average CS of the chemically strengthened ultrathin glass has a residual rate of ≥88% at 300℃ / 1h, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass.
[0184] In some embodiments, the residual average CS of the chemically strengthened ultrathin glass at 300°C / 1h can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98%, or it can be a value within a range defined by any two of the above specific values as endpoints, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened ultrathin glass with the desired performance of this application is obtained.
[0185] The ultra-thin glass or chemically strengthened ultra-thin glass with excellent performance provided in this application can be used in flexible and foldable electronic devices, displays, sensors, semiconductor packages, or thin-film batteries. For example, it can be used in the fields of cover plates and substrates for flexible and foldable electronic devices, such as flexible substrates for holding or mounting components in fragile sensors, fingerprint sensors, image sensors, display covers, screen protectors, curved displays, wearable devices, or flexible electronic devices. It can also be used in applications such as display substrates or protective covers, fingerprint sensor covers, general sensor substrates or covers, cover glass for consumer electronics, protective covers for displays, and other surfaces, especially curved surfaces. It can also be used in applications such as display substrates and covers, fingerprint sensor module substrates or covers, semiconductor packages, thin-film battery substrates and covers, and foldable displays. For example, it can be used as a coating for resistive touchscreens, and as a consumable protective film for displays, mobile phones, cameras, gaming device accessories, tablets, laptops, televisions, mirrors, windows, aviation windows, furniture, and white goods.
[0186] The ultrathin glass or chemically strengthened ultrathin glass with excellent properties provided in this application can also be used to manufacture glass devices. The glass devices referred to herein can be regular or irregular, and can be manufactured according to the needs of those skilled in the art.
[0187] For example, the ultra-thin glass or chemically strengthened ultra-thin glass with excellent performance provided in this application can be used to manufacture cover glass, which can be a display screen cover, back cover, or camera protective cover for electronic devices. For example, the ultra-thin glass or chemically strengthened ultra-thin glass with excellent performance provided in this application can be used in electronic devices. (Reference) Figure 2 and Figure 3This application provides an electronic device, which can be a mobile phone, tablet computer, smart wearable device, or other electronic product. The electronic device includes a casing assembled on the outside of the device, and components such as a circuit board and battery located inside the casing. The casing includes a display screen cover 11 assembled on the front and a rear cover 12 assembled on the rear. The display screen cover 11 covers the display module. The display screen cover 11 and / or the rear cover 12 are made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass. In this application, the display screen cover 11 and the rear cover 12 can be entirely made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass, or only partially made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass. In this application, the display screen can be a touch screen, and the display screen cover 11 can be a protective cover disposed on the touch screen. In this application, the rear cover 12 can only cover the rear side of the electronic device (and the side facing away from the display screen), or it can simultaneously cover the rear side and side bezels of the electronic device. Optionally, the rear cover 12 can cover all side bezels around the electronic device, or it can cover only part of the side bezels.
[0188] In some embodiments of this application, such as Figure 3 As shown, the electronic device also includes a camera assembly located inside the housing. The housing may include a camera protective cover 13, which covers the camera assembly to protect it. The camera protective cover 13 may be made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass. In this embodiment, the camera protective cover 13 may be partially or entirely made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass. In this embodiment, the location of the camera protective cover 13 depends on the location of the camera assembly; it may be located on the front or rear of the electronic device. In some embodiments of this application, the camera protective cover 13 may be a separate structure from the display cover 11 or the rear cover 12. In other embodiments of this application, the camera protective cover 13 may be an integral structure with the display cover 11 or the rear cover 12.
[0189] In the embodiments of this application, the display screen cover, back cover, and camera protective cover in the electronic device may be made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass, or any two of them may be made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass, or all three may be made of the aforementioned ultra-thin glass or chemically strengthened ultra-thin glass.
[0190] In some embodiments of this application, the display screen cover, back cover, or camera protective cover in the electronic device can be 2D, 2.5D, 3D, or irregularly shaped. In some embodiments of this application, the display screen cover, back cover, or camera protective cover in the electronic device can be of uniform thickness or of unequal thickness.
[0191] The technical solutions of this application will be further described in detail below with reference to the embodiments. The embodiments of this application described in detail below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0192] Example 1 (1) Preparation of ultrathin glass: According to the glass composition in Table 1, weigh out each raw material according to the molar percentage of each oxide, prepare 1000 kg of raw material, and then mix it with a V-type mixer at a speed of 25 r / min for 300 minutes to obtain a uniformly mixed raw material mixture.
[0193] The homogenized raw material mixture was transferred to a melting furnace and melted at 1650℃ for 10 hours. The molten glass then entered a platinum channel for clarification and homogenization. The homogenized molten glass then flowed from a narrow slit in a platinum baffle plate below into a crucible furnace. It was then drawn thin into ultra-thin glass by a drawing machine and traction rollers. Next, it underwent a first annealing at 580℃ for 12 hours, followed by furnace cooling to room temperature. A second heating and annealing process was then performed to obtain the raw glass material. This material was then cut to obtain ultra-thin glass samples of fixed dimensions: 140 mm x 70 mm, with a thickness of 0.03 mm. The process parameters for the heating and second annealing are shown in Table 3.
[0194] The other embodiments and comparative examples all prepared ultrathin glass in the same manner as in Example 1, except that the composition and formulation of each embodiment and comparative example are shown in Table 1 and Table 2.
[0195] The optical properties and surface roughness of the ultrathin glass were tested, and the results are shown in Table 3.
[0196] It should be understood that, based on the molar percentage of oxides, the composition of the ultrathin glass prepared in each embodiment and comparative example is substantially the same as that of the glass composition, except for clarifying agents and unavoidable impurities totaling no more than 1%.
[0197] (2) Preparation of chemically strengthened ultrathin glass: The ultrathin glass polished sheet samples obtained above were subjected to one-step strengthening in a molten salt bath. The salt bath was 100% KNO3, the strengthening temperature was 380℃, and the strengthening time was shown in Table 4.
[0198] All other embodiments and comparative examples were chemically strengthened using the same strengthening process.
[0199] It should be understood that, based on the molar percentage of oxides, the composition of the center or tensile stress layer of the chemically strengthened ultrathin glass prepared in the examples and comparative examples is substantially the same as the composition of the glass composition, except for clarifying agents and unavoidable impurities totaling no more than 1%.
[0200] The stress characteristics (surface CS, DOL_0), CS reduction rate and CS residual rate of the chemically strengthened ultrathin glass provided in each embodiment and comparative example were tested, and the results are shown in Table 4.
[0201] Table 1
[0202] Table 2
[0203] In the table, [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the composition of the ultrathin glass, respectively.
[0204] Table 3
[0205] Table 4
[0206] In the table, the CS decrease rate refers to the CS decrease rate in the same group of experiments. The CS decrease rate is calculated as (CS maximum value - CS minimum value) / CS maximum value × 100%. The same group of experiments refers to experimental groups that use the same formula and the same preparation process (without chemical strengthening process). For example, Examples 1-1, 1-2 and 1-3 are the same experimental group.
[0207] As shown in the table above, the ultrathin glass provided in this application has high surface compressive stress and a mild stress decay curve after chemical strengthening, and has a good surface compressive stress residual rate under high temperature conditions, which is beneficial for the product to maintain high strength during high temperature or long-term use.
[0208] The comparative data shows that when the composition of ultrathin glass does not meet a specific range, or the composition of a specific content does not meet a specific relationship, or a specific heating and second annealing process is not used, the chemically strengthened ultrathin glass produced will either have a lower surface compressive stress, a higher CS reduction rate, or a lower CS residual rate.
[0209] For example, data from Comparative Examples 1-1 to 2-3 show that although the composition of the ultrathin glass is within a specific range and satisfies a specific relationship, it does not employ a specific heating and second annealing process. As a result, the resulting chemically strengthened ultrathin glass has lower surface compressive stress, higher CS reduction rate, and lower CS residual rate.
[0210] For example, data from Comparative Examples 3-1 to 10-3 show that the components of ultrathin glass do not satisfy a specific relationship. The chemically strengthened ultrathin glass produced by this method either has a low surface compressive stress, a high CS reduction rate, or a low CS residual rate.
[0211] For example, data from Comparative Examples 11-1 to 11-3 show that if the composition of the ultrathin glass does not meet a specific range, the resulting chemically strengthened ultrathin glass will have lower surface compressive stress and a higher CS reduction rate.
[0212] The above are merely specific embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing ultrathin glass, characterized in that, The method includes: The glass composition raw materials are melted to obtain a molten liquid; The molten liquid is molded in one step and then subjected to a first annealing to room temperature to obtain an intermediate product; The intermediate product is heated and subjected to a second annealing to room temperature to obtain ultrathin glass; The heating endpoint temperature is 450℃~600℃, the heating holding time is 1h~10h, and the cooling rate of the second annealing is 10℃ / h~300℃ / h.
2. The method for preparing ultrathin glass according to claim 1, characterized in that, The endpoint temperature of heating, the holding time of heating, the cooling rate of the second annealing, and the endpoint temperature of the second annealing can be obtained by the following formula: Where CS is the target compressive stress of the target chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, and t is the time in h. Furthermore, the final heating temperature, the holding time during heating, the cooling rate of the second annealing, and the final temperature of the second annealing can be obtained by the following formula: , t eff =t h +t eq , , Where CS is the target compressive stress of the chemically strengthened ultrathin glass, T is the final heating temperature in °C, A is the pre-exponential factor in MPa, α is the time exponent, β is the temperature correlation coefficient in K, th is the heating holding time in h, and T end γ is the endpoint temperature of the second annealing in °C, v is the cooling rate of the second annealing in °C / h, γ is the equivalent temperature constant related to the relaxation activation energy in K, and t is the integral variable in h. Among them, A, α, β, γ are determined using a global nonlinear regression method.
3. The method for preparing ultrathin glass according to any one of claims 1 to 2, characterized in that, The composition of the ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
4. The method for preparing ultrathin glass according to any one of claims 1 to 3, characterized in that, The composition of the ultrathin glass satisfies: 0.80≤[MgO] / [ZrO2] ≤2.00, preferably, 0.90≤[MgO] / [ZrO2] ≤1.90; and / or, 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) ≤2.00; and / or, 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50; and / or, 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35, preferably, 0.15≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35; and / or, [B₂O₃] + [CaO] + [K₂O] ≤ 3.00%; Wherein, [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the composition of the ultrathin glass, respectively.
5. An ultrathin glass, characterized in that, The ultrathin glass is produced by reheating an intermediate product that has been formed in one step and annealed to room temperature to 450°C to 600°C and holding it at that temperature for 1 hour to 10 hours, followed by a second annealing to room temperature at a cooling rate of 10°C / hour to 300°C / hour. The composition of the ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
6. The ultrathin glass according to claim 5, characterized in that, In the ultrathin glass, by mass percentage of oxides, The SiO2 content is 53.50%~60.00%; and / or, The Al2O3 content is 17.50%~24.50%; and / or, The Na₂O content is 15.50%~18.50%; and / or, The K2O content is 0~1.20%; and / or, The MgO content is 1.50%~3.00%; and / or, The ZrO2 content is 1.50%~2.00%; and / or, The Y2O3 content is 0~1.00%; and / or, The B2O3 content is 0~1.00%; and / or, The CaO content is 0~0.80%; and / or, The P2O5 content is 0~1.00%.
7. The ultrathin glass according to any one of claims 5 to 6, characterized in that, The composition of the ultrathin glass satisfies: 0.80≤[MgO] / [ZrO2] ≤2.00, preferably, 0.90≤[MgO] / [ZrO2] ≤1.90; and / or, 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) ≤2.00; and / or, 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50; and / or, 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35, preferably, 0.15≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35; and / or, [B₂O₃] + [CaO] + [K₂O] ≤ 3.00%; Wherein, [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the composition of the ultrathin glass, respectively.
8. The ultrathin glass according to any one of claims 5 to 7, characterized in that, The thickness of the ultrathin glass is 0.03mm to 0.5mm; and / or, The arithmetic mean roughness Ra of the surface of the ultrathin glass after one-time molding is ≤1 nm, preferably ≤0.7 nm; and / or, The ultrathin glass is transparent in the visible light range. Preferably, when the thickness of the ultrathin glass is 0.03mm to 0.5mm, the transmittance of the ultrathin glass at a wavelength of 550nm is ≥91.50%; and / or, When the thickness of the ultra-thin glass is 0.03mm to 0.5mm, the haze of the ultra-thin glass is ≤0.2%.
9. A chemically strengthened ultrathin glass, characterized in that, The chemically strengthened ultrathin glass is obtained by chemically strengthening ultrathin glass. The ultrathin glass is obtained by reheating an intermediate product that has been formed in one step and annealed to room temperature to 450°C~600°C and holding it at that temperature for 1h~10h, and then annealing it to room temperature at a cooling rate of 10°C / h~300°C / h. The chemically strengthened ultrathin glass includes a compressive stress layer and a tensile stress layer; The composition of the chemically strengthened ultrathin glass tensile stress layer or the composition of the center of the chemically strengthened ultrathin glass, based on the mass percentage of oxides, includes: SiO2: 53.00%~61.00%, Al2O3: 17.00%~25.00%, Na2O: 15.00%~20.00%, K2O: 0~1.50%, MgO: 0.50%~3.00%, ZrO2: 0.50%~2.50%, Y2O3: 0~2.00%, B2O3: 0~2.00%, CaO: 0~1.00%, and P2O5: 0~1.00%.
10. The chemically strengthened ultrathin glass according to claim 9, characterized in that, The composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass, based on the mass percentage of oxides, The SiO2 content is 53.50%~60.00%; and / or, The Al2O3 content is 17.50%~24.50%; and / or, The Na₂O content is 15.50%~18.50%; and / or, The K2O content is 0~1.20%; and / or, The MgO content is 1.50%~3.00%; and / or, The ZrO2 content is 1.50%~2.00%; and / or, The Y2O3 content is 0~1.00%; and / or, The B2O3 content is 0~1.00%; and / or, The CaO content is 0~0.80%; and / or, The P2O5 content is 0~1.00%.
11. The chemically strengthened ultrathin glass according to any one of claims 9 to 10, characterized in that, The composition of the chemically strengthened ultrathin glass tensile stress layer or the composition at the center of the chemically strengthened ultrathin glass satisfies the following: 0.80≤[MgO] / [ZrO2] ≤2.00, preferably, 0.90≤[MgO] / [ZrO2] ≤1.90; and / or, 1.40≤([Al2O3]+1.5×[MgO]+2×[ZrO2]) / ([Na2O]+0.5[K2O]) ≤2.00; and / or, 0.30≤([Al2O3]+[MgO]-0.4×[K2O]) / [SiO2]≤0.50; and / or, 0.10≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35, preferably, 0.15≤([Al2O3]+2.5×[ZrO2]-0.7×[Na2O]) / [SiO2]≤0.35; and / or, [B₂O₃] + [CaO] + [K₂O] ≤ 3.00%; Wherein, [MgO], [ZrO2], [Al2O3], [Na2O], [K2O], [SiO2], [B2O3], and [CaO] refer to the mass percentages of MgO, ZrO2, Al2O3, Na2O, K2O, SiO2, B2O3, and CaO in the composition of the tensile stress layer of the chemically strengthened ultrathin glass or in the composition at the center of the chemically strengthened ultrathin glass.
12. The chemically strengthened ultrathin glass according to any one of claims 9 to 11, characterized in that, The thickness of the chemically strengthened ultrathin glass is 0.03 mm to 0.5 mm; and / or, When the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has an average CS of ≥1000 MPa, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass. Preferably, the chemically strengthened ultrathin glass has an average CS of 1020 MPa to 1250 MPa; and / or, When the thickness of the chemically strengthened ultrathin glass is 0.03 mm, the chemically strengthened ultrathin glass has a DOL_0 of ≥5.0 μm, where DOL_0 is the compressive stress layer depth. Preferably, the chemically strengthened ultrathin glass has a DOL_0 of 5.0 μm to 11.0 μm.
13. The chemically strengthened ultrathin glass according to any one of claims 9 to 12, characterized in that, When strengthened in pure KNO3 molten salt at 380℃, and when the strengthening time is extended from 20 min to 60 min, the average CS decrease rate of the chemically strengthened ultrathin glass is ≤ 2.5%, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass, preferably ≤ 2.0%; and / or, When strengthened in pure KNO3 molten salt at 380℃, and when the strengthening time is extended from 20 min to 60 min, the DOL of the chemically strengthened ultrathin glass increases by ≥ 2.0 μm, where DOL_0 is the compressive stress layer depth; and / or, The average CS of the chemically strengthened ultrathin glass has a residual rate of ≥88% at 300℃ / 1h, where CS refers to the surface compressive stress of the chemically strengthened ultrathin glass.
14. A cover glass, characterized in that, The cover glass includes ultrathin glass produced by the method of any one of claims 1 to 4, ultrathin glass as described in any one of claims 5 to 8, or chemically strengthened ultrathin glass as described in any one of claims 9 to 13.
15. An electronic device, characterized in that, The electronic device includes ultrathin glass produced by the method of any one of claims 1 to 4, ultrathin glass as claimed in any one of claims 5 to 8, or chemically strengthened ultrathin glass as claimed in any one of claims 9 to 13.
16. The electronic device according to claim 15, characterized in that, The electronic device includes a housing assembled on the outside of the electronic device, the housing comprising ultrathin glass produced by the method of any one of claims 1 to 4, ultrathin glass as claimed in any one of claims 5 to 8, or chemically strengthened ultrathin glass as claimed in any one of claims 9 to 13.
17. The electronic device according to claim 16, characterized in that, The housing includes a display cover assembled on the front side of the electronic device, the display cover comprising ultrathin glass produced by any one of claims 1 to 4, ultrathin glass as claimed in any one of claims 5 to 8, or chemically strengthened ultrathin glass as claimed in any one of claims 9 to 13.
18. The electronic device according to claim 15, characterized in that, The electronic device includes a foldable electronic device, a display, a sensor, a semiconductor package or a thin-film battery. Preferably, the sensor includes a fragile sensor, a fingerprint sensor or an image sensor. Preferably, the ultra-thin glass or the chemically strengthened ultra-thin glass is applied to the substrate or cover of the electronic device.